Spheres and folds: the applicability of fichtean biopolitcs to Deleuze - Ferreyra, Julián (Estudios de Filosofía, 2018)
This paper aims to construct an affirmative biopolitics through the confrontation of the political ontologies of Johann Fichte and Gilles Deleuze. We will show the affinity between the Thathandlung and four Deleuzian concepts that are interwoven throughout his work: eternal return, intensity, affectus and fold. However, both transcendental philosophies differ in their conception of time: Fichte opposes the agility of the pure activity of the I (eternal) with the in exibility of the practical-political determinations (temporal), whereas Deleuze’s philosophy realizes the immanence of both realms. Ficthean inflexibility is observable in the realm of applicability (the body as the sphere of action) and determines its conception of the State. Therefore, to conclude, an applicability based on the form of the fold enables us to propose a Deleuzian form of State that may be effective faced with the challenges of the contemporary world.